Tinjauan Terhadap Hukum Persaingan Usaha Di Indonesia Dari Perspektif Hukum Perlindungan Konsumen - Apriani, Desi (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2019)
The business world is something that cannot be separated from business competition. There are business actors who compete in a fair competition and there are also business actors who compete in a unfair competition. This is where the importance of the presence of business competition law in a country. In Indonesia, business competition law is contained in Law Number 5 of 1999 which prohibits monopolistic practices and unfair business competition. In relation to consumer protection, Law Number 5 Year 1999 has the aim of protecting the public interest and seeking public welfare. The prohibitions in the law indirectly have a protected effect on consumer interests. Need consistency in enforcement of business competition law so that the goal of protecting consumers can be achieved optimally.